(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
Dissolution test methods described in the pharmacopeias were developed mainly for solid oral dosage forms or transdermal drug delivery systems. Dissolution studies of other dosage forms, such as suspensions, are challenging and may require special dissolution equipment that is not commercially available. 3D printing represents a way to close this gap by providing the opportunity to easily produce custom-made adapters. In this work, adapters for dialysis membranes and molds for producing hydrogels incorporating suspensions were manufactured with stereolithography. The adapters were tested in combination with different monographed dissolution apparatuses to study release from a model drug suspension. The hydrogels led to a slower dissolution than the direct injection into the dissolution medium. Agarose-based hydrogels, with their interconnected pores and potential to regulate drug release, proved to slow down the dissolution process and provide a controlled environment. Using dialysis membranes slowed down the dissolution even more. To investigate the impact of the dialysis membrane properties, different molecular weight cut-offs were used. The molecular weight cut-off did not impact the dissolution speed for the tested paracetamol suspension. The agarose concentration in the hydrogels was also no factor in dissolution speed. The described methods could be of further interest in investigating poorly soluble drugs resulting in a more extended dissolution profile. Acknowledgments The authors thank Ever Pharma and Zoltan Tölgyesi for providing materials and scientific input for this work. Author’s statement The authors state no conflict of interest. Informed consent has been obtained from all individuals included in this study.